EVALUASI PROGRAM P5 (PROYEK PENGUATAN PROFIL PELAJAR PANCASILA) KELAS V SD NEGERI SIDOREJO LOR 03 SALATIGA MENGGUNAKAN DISCREPANCY EVALUATION MODEL - Rizki Novayanto; Mawardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to evaluate the P5 program (pancasila student profile strengthening project) for grade V at Sidorejo Lor 03 Salatiga State Elementary School using the Discrepancy evaluation model. This research is a mixed method research with evaluation model. The subjects of this research are the principal and the fifth grade teacher of Sidorejo Lor 03 Salatiga State Elementary School. The data collection techniques used questionnaires, observation interviews, and document studies. Data analysis techniques used quantitative and qualitative data analysis techniques. The results showed that the P5 program implemented in SD Negeri Sidorejo Lor 03 Salatiga has run well. This is indicated by the percentage of gaps in the design aspect 16.6% installation aspect 8.3% process aspect 3.2% product aspect 12.5% and cost benefit aspect 12.5%.